Chapter 1 Introductions Critical pedagogy and the intersectional complexities of names - Harmat, Gal (Taylor & Francis, 2020)
This introduction will not simply introduce the topic of the book as a classical introduction. Instead, it will combine the first chapter of the book with introduction by focusing on how to start a workshop or a course. This is the way I often open my courses and learning workshops. We will begin, then, by examining the very concept of introductions in the widest sense, with a special focus on the function of names: the names that individuals are given at birth, usually by their parents or extended family, and that are often chosen because of their significance. People's names are imbued with meaning, with symbolism, with cultural- and often religious-meaning, which for some may carry positive connotations while others may find a certain name at best aseptic or, at worst, frightening. And in most cases, your name is the first aspect of your person that others experience.